2014
DOI: 10.4028/www.scientific.net/amr.880.42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen on Plastic Strain Localization of Construction Steels

Abstract: The effect of interstitial hydrogen atoms on the mechanical properties and plastic strain localization patterns in tensile tested specimens of austenitic stainless and low-carbon steels have been studied using a double exposure speckle photography technique. The main parameters of plastic flow localization at various stages of the deformation hardening have been determined in steels electrolytically saturated with hydrogen in a three electrode electrochemical cell at a controlled constant cathode potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The comparison of the data for the two conditions (the initial condition and one after hydrogenation) of Fe-0.07%C steel showed that the localized plasticity sites have been formed and evolved throughout the plastic flow process during tensile testing. Hydrogen enhances localization and changes the quantitative parameters of macroscopic plastic strain localization: the length and the velocity of autowaves plastic strain localization [9,11]. The mechanism of hydrogen-stimulated plastic strain localization is still under discussion [6].…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of the data for the two conditions (the initial condition and one after hydrogenation) of Fe-0.07%C steel showed that the localized plasticity sites have been formed and evolved throughout the plastic flow process during tensile testing. Hydrogen enhances localization and changes the quantitative parameters of macroscopic plastic strain localization: the length and the velocity of autowaves plastic strain localization [9,11]. The mechanism of hydrogen-stimulated plastic strain localization is still under discussion [6].…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the data for the two conditions (initial condition and after hydrogenation) of steel Fe-0.07%C showed that the localized plasticity sites have been formed and evolved throughout of the plastic flow process during tensile. Hydrogen enhances localization and changes the quantitative parameters of the macroscopic plastic strain localization: the length and the velocity of autowaves plastic strain localization [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Pouring a liquid metal onto a solid plate placed in a mold is frequently utilized for producing various bimetals [15]. The electrolytic hydrogenation of bimetal samples was carried out within 6 hours under a controlled cathode potential of -600 mV relative to a reference electrode of silver chloride in 0.1N sulphuric acid solution with addition of 20 mg/L of thiourea [16]. The current-voltage curves were obained on an IPC-Compact potentiostat.…”
Section: Methodsmentioning
confidence: 99%